Cultural Dimensions Toward The Communication Policy of Street Vendors Relocation in The Government of Yogyakarta City - LA MANI; BUDI GUNTORO; MUDIYONO MUDIYONO; NUNUNG PRAJARTO (Jurnal Studi Pemerintahan, 2016)
Culture appears in all contexts of human life, included in the government's communication policy. The aim of this study is to verify the influence of the cultural dimension toward the communication policy of relocating street vendors by the Government of Yogyakarta City in 2004 to 2010. This study used 258 vendors who had been relocated as the sample. The data analysis used of this study was quantitative with the double regression analysis test.  The results of this study showed that the cultural dimension have a significant effect toward the communication of relocation policy of Street Vendors in Yogyakarta. It can be seen from the F-count (71,536) F-table (4,710), t-count (18,625) t-table (1,960) with a significance level of 0.000 (α 0,05). The regression determination coefficient (R2) showed that the communication of relocation policy of street vendors in Yogyakarta is influenced by the cultural dimension, that is about 0,600, or 60%, while the rest is about 40% due to other variables outside of the model studied.Keywords: cultural dimension; communication; relocation policy; street vendor